PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN STUNTING DI DESA KOTO AGUNG KECAMATAN KELILING DANAU KABUPETEN KERINCI - M Dhany Al Sunah (Bajang Institute, 2022)
Stunting is still a public health problem in developing countries such as Indonesia with a fairly high prevalence. Stunting is caused by lack of nutritional intake for a long time in the first 1000 days of life (HPK) which is a period of fulfilling nutrition for toddlers. The 2005 WHO-MGRS (Multicentre Growth Reference Study) standard showed that a z-score value less than -2SD was categorized as short, and categorized as very short if the z-score value was less than -3SD. It is known that they have not been widely exposed to stunting so that some of them think that their children / toddlers are shorter than their age is a genetic factor so they do not require further treatment. Koto Agung Village, is an area within the scope of the Jujun Health Center area. People in Koto Agung Village have varying ages ranging from infants and toddlers who are targeted in community service activities as well as throughout the life cycle who come from permanent residents of Koto Agung Village and migrants who live in Koto Agung Village, Keliling Danau District. The community or parents of babies and toddlers in Koto Agung Village mostly have upper secondary education, both mothers and fathers. The method of implementation in the community service program is through providing counseling about stunting to mothers in the Koto Agung Village area through 3 (three) stages, namely implementation strategy meetings, site surveys and preparation of facilities and infrastructure. The results of the implementation of Community Service activities are as follows: Most of the parents and community of Koto Agung Village have secondary education. Parents' knowledge about the stunting prevention program based on the results of the pre-test, most of the pregnant women did not know about the stunting prevention program, while based on the post-test results, almost all parents already understood the implementation of the stunting program